Upward-and-downward spread of smoldering peat fire - Huang,X; Rein,G (Proceedings of the Combustion Institute, 2019)
Smoldering is the dominant combustion process in peat fire, releasing a large amount of carbon and smoke into the atmosphere. The spread of smoldering in peatland is a multi-dimensional process, which is slow, low-temperature, persistent, and difficult to detect. In this work, we investigate the upward spread of peat fire from the underground to the surface after forced ignition which is a relevant configuration but rarely studied. In the experiment, ignition is not possible if the igniter is deeper than 15cm below the free surface, regardless of moisture content or density. Once ignited, the 1st-stage upward fire spread is initiated towards the free surface (opposed smoldering) with a peak temperature of 300°C, leaving behind a char structure that does not collapse. Then, a 2nd-stage downward spread (forward smoldering) is activated with a peak temperature of 600°C and regression of free surface. The upward spread is faster than the downward spread. The rates of both upward and downward spread decrease as the peat density or depth is increased. These experimental observations are successfully captured by a 1D computational model of heat and mass transfer with 5-step kinetics. Modelling results further suggest that (1) the oxygen diffusion controls the entire upward-to-downward spread of peat fire, (2) the oxidation of peat sustains the 1st-stage upward spread, and (3) the oxidation of char sustains the 2nd-stage downward spread. This is the first study investigating the upward spread of peat fire, which helps understand the persistence of peat fire and guide the fire prevention and suppression strategies.